A review of the international framework for access and benefit sharing of genetic resources with special reference to the Nagoya Protocol - Ansari, Abdul Haseeb; Laxman, Lekha (Australian Centre for Climate and Environment, 2013)
The effective implementation of the Convention on Biological Diversity’s objective of ‘fair and equitable sharing of the benefits arising out of the utilization of genetic resources’ is vital for the realisation of its two other objectives: ‘the conservation of biological diversity’ and ‘the sustainable use of its components’. ‘Green developmentalism’ through the application of market instruments to nature is expected to impede the loss of global biodiversity. The Nagoya Protocol on Access and Benefit Sharing of Genetic Resources is also premised upon the idea that market instruments can achieve optimal allocation of the benefits of nature. This article revisits the road of access and benefit sharing from the Convention on Biological Diversity to the Nagoya Protocol. It includes a preliminary overview of the provisions of the Nagoya Protocol and the risks associated with ‘commodification of nature’ in addressing global inequalities arising from uneven markets. The article also explores measures that can be jointly undertaken by the global community to ensure that access and benefit sharing of genetic resources is undertaken in a fair and equitable manner.